Caveolae and lipid rafts : roles in signal transduction and the pathogenesis of human disease - Frank, Philippe G.; Lisanti, Michael P. (Advances in molecular and cell biology, 2005)
The first book available dedicated to caveolae in human diseases and cellular metabolism.